2012
DOI: 10.4103/1947-2714.98589
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malnutrition among the mising children of Northeast India: A comparison between four different sets of criteria

Abstract: Background:Prevalence of malnutrition among the children from developing countries has reached unprecedented level which can be evaluated by body mass index.Aim:This study was designed to determine the prevalence of malnutrition among the Mising children of Northeast India using four different sets of Body Mass Index references.Materials and Methods:A cross-sectional study was performed on a population representative sample of 511 Mising children. Four different sets of Body Mass Index reference were used to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…This prevalence is lower than that observed in India (13) and Morocco (14) but close to that found in Algeria (Sidi-bel-Abbes) in 2008 (15).…”
Section: Discussionsupporting
confidence: 58%
“…This prevalence is lower than that observed in India (13) and Morocco (14) but close to that found in Algeria (Sidi-bel-Abbes) in 2008 (15).…”
Section: Discussionsupporting
confidence: 58%
“…It is important to note that this scoping review did not assess the quality of undernutrition indicators measured in the included publications; consequently, prevalence could have been overestimated or underestimated. Six publications nevertheless assessed and compared prevalence of stunting and/or thinness using different growth references (46,(49)(50)(51)(52)(53) . The review findings showed that prevalence depended substantially on the growth reference used.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of stunting ranged from 7% (46) to 90% (47) , and prevalence of thinness varied from 1•3% (30) to 63% (48) . Some publications determined prevalence of stunting and/or thinness with different growth references (46,(49)(50)(51)(52)(53) . On the one hand, the prevalence of nutritional status varied greatly with the growth reference employed.…”
Section: 24mentioning
confidence: 99%
“…Sikdar's study revealed a prevalence of overweight even lower in individuals 10 years of age according to WHO criteria (9.6% in boys and 8% in girls). [ 23 ]…”
Section: Discussionmentioning
confidence: 99%